Utilization of Skilled Birth Attendants among Women of Reproductive Age in Central Division, Kajiado County Kenya - Okoth, Consolate Awuor (My University, 2014)
The proportion of births assisted by skilled birth attendants in Kenya is 44% while in Kajiado Central Sub County is 28%. Maternal mortality in Kenya is estimated to be 488 per 100,000 live births. This worrying trend of maternal mortality is thought to be a result of using unskilled attendants at birth. This study sought to determine the factors that influenced utilization of skilled birth attendants among women of reproductive age in Central division, Kajiado County. The objectives of the study were to: determine demographic characteristics, socio-cultural factors, economic factors as well as institutional characteristics that influenced utilization of skilled birth attendants among women of reproductive age in Central Division. A cross sectional descriptive study design was used. The study employed both qualitative and quantitative data collection techniques. Data was collected using semi-structured questionnaires, key informant interviews and focused group discussions. A total of 324 out of a sample population of 332 women of reproductive age who met the inclusion criteria were recruited for the study using systematic sampling of households. Informed consent was obtained from respondents. The respondents were assured of privacy and confidentiality. Quantitative data was analyzed using SPSS version 16 while qualitative data was organized and analyzed thematically. Hypothesis testing was done using Chi-square test. A p-value of <0.05 was considered significant. The study findings show a low level of utilization of skilled birth attendants (42%) among women of reproductive age in Central Division. The main determinants of utilization of SBAs were residence OR=0.038 (0.020-0.074), p<0.001, parity OR = 0.219 (0.118-0.405), p<0.001, births in past five years OR = 0.336 (0.204-0.767), p< 0.001, occupation OR = 0.383 (0.138-1.064), p=0.002 and cost of delivery OR=0.546(0.166-1.799). Others were husband‟s occupation OR=1.848 (0.991-3.446), p=0.001, monthly income OR=4.593 (2.296-9.190), p<0.001, husband‟s education OR=4.992 (2.285-10.907), p<0.001 and respondent‟s education OR= 6.703 (3.473-12.937), p<0.001.The study recommends that local leaders should encourage universal education of the girl child; MOH needs to carry out behavior change communication at individual and community levels to address socio-cultural practices that are barriers to the uptake of SBA services; county government to improve infrastructure especially in remote areas that are hard to reach; need to improve economic status of women to empower them economically; health care interventions to put emphasis on access and availability of services especially in rural areas and finally the MOH should provide mobile health care services and outreaches to remote villages and those difficult to reach.